AS . biuletyn pism związkowych i zakładowych, no. 45, 1981 - Agencja Prasowa "Solidarność", [ed. Bohdan Bielski] (Agencja Prasowa AS z siedzibą w "Mazowszu", 1981)
Creation and circulation: Publication contains reprints of trade union documents and articles from the trade union press.